AERIAL COMPUTER VISION FOR A 3D VIRTUAL HABITAT. - Leberl, Franz; Bischof, Horst; Pock, Thomas; Irschara, Arnold; Kluckner, Stefan (Computer (00189162), 2010)
The article discusses the creation of three-dimensional (3D) images of the world, which include natural and mad-made objects such as buildings using aerial maps. Phogrammetric research has reduced the cost of producing 3D images and advances in technology also provided more affordable storage space. Digital cameras continue to progress in terms of image resolution and operation has been significantly automated, contributing to the cost reduction. The use of scanning equipment using light detection and range (LIDAR) technology is also cited.